Safety and efficacy of oil palm phenolic supplementation in improving lipid profile among hyperlipidemic adults: a phase 2, randomized, double-blind, placebo-controlled clinical trial - Muhammad Ismail Tadj, Nur Balqis; Ibrahim, Nurul `Izzah; Tg Abu Bakar Sidik, Tg Mohd Ikhwan; Zulfarina, Mohamed S.; Haji Mohd Saad, Qodriyah; Leow, Soon-Sen; Fairus, Syed; Naina Mohamed, Isa (Frontiers in Pharmacology, 2023)
Introduction: Oil palm phenolic (OPP) is an antioxidant aqueous palm oil by-product and contains a high amount of phenolics. OPP has been proven to have many therapeutical benefits, and one of them is as an antihyperlipidemic agent. The previous phase 1 clinical trial proved OPP was safe to be orally consumed by healthy volunteers and yielded a good lipid profile. Thus, this phase 2 clinical trial was conducted to determine the effectiveness of OPP in improving the lipid profile among hyperlipidemic subjects. Methods: A parallel, placebo-controlled, randomized, double-blinded clinical trial was conducted for 2 months on 50 hyperlipidemic subjects aged 20−50 years old. This trial was registered at clinicaltrials.gov (NCT04573218). The subjects were randomly distributed to two treatment arms with 25 participants each: control/placebo (11 males & 14 females) and 250 mg of OPP (10 males &15 females). The subjects were required to consume one capsule per day for 60 days. Fasting blood sampling for routine blood profile (hematology, liver function, renal function, and lipid) analysis and a medical examination were conducted at baseline, day 30, and day 60. T-test analysis was used to compare the difference between two test groups. Results: The baseline lipid profile between control group (